Calcinosis Cutis of the Nasal Dorsum. Issue 2 (17th February 2022) - Marsh, Henry R.; Miyake, Bradley A.; Alamiri, Nasser N.; Mims, Mark M.
Abstract : Summary: Calcinosis cutis is a common dermatological problem in patients with systemic sclerosis, dermatomyositis, and systemic lupus erythematous; however, it is rare to occur outside of these diseases. It represents a multidisciplinary problem that involves primary care physicians, dermatologists, and surgeons. The pathophysiology is defined by deposition of calcium salts in the subcutaneous tissue as hydroxyapatite, but the underlying mechanism has yet to be determined. The most common locations of lesions are the scalp, scrotum, extremities, and joints. Rarely does calcinosis cutis occur on the face. We present a unique case of idiopathic calcinosis cutis that occurred in a healthy patient with normal serum calcium and phosphate levels on the nasal dorsum, which was managed surgically. The histology of the calcinosis showed normal morphology, dominated by large deposits of calcium and normal surrounding tissues. This case represents a rare but clinically relevant presentation of idiopathic calcinosis cutis in an otherwise healthy individual.